Consumerism in Personal Finance: An Islamic Wealth Management Approach - Farisah Amanda; Bayu Taufiq Possumah; Achmad Firdaus (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
Consumerism phenomenon has been noticed from various points of view, such culture, psychology, and sociology but rarely linked to personal finance using Islamic wealth management approach. The aims of this study are to understand the causes and impacts of consumerism on personal finance and find the solution to this problem by using Islamic wealth management. By using thematic analysis this study reviewing consumerism from the perspective of personal finance in Islamic wealth management approach. This study found that the causes of consumerism involve both external and internal factors. The impacts of consumerism on personal finance are the debt trap, no productive and charity allocation. An exact number of maximum consumption cannot be set for every individual or family, but they are all agreed that allocating income should be based on the right priority scale. The second finding is we propose Islamic Wealth Management (IWM) approaches in reducing the problem of Consumerism.DOI: 10.15408/aiq.v10i2.5518